The expression of genes in different sites of gut tract regulates the meat quality of semitendinosus muscle in sheep and goats - Chen, Binlong; Huang, Zhiying; Cai, Zhongkun; Li, Siyu; Yan, Guangwen; Chang, Weihua; Zhang, Yi; Yang, Shizhong (Frontiers in Veterinary Science, 2025)
IntroductionFor small ruminants, meat quality—an economically significant characteristic—results from the combined effects of genetic, dietary, and physiological elements. However, the contribution of gastrointestinal (GI) tract gene expression to meat quality remains unclear.MethodsHere, we performed bulk RNA-seq on 130 samples from Liangshan Black Sheep and Meigu Black Goats, including 10 GI tract segments and semitendinosus muscle, integrating these data with measurements of amino acid composition, fatty acid profiles, and volatile flavor compounds.Results and discussionWe found distinct, segment-specific transcriptional programs across the GI tract, with major functional shifts at the rumen–reticulum, omasum–abomasum, and abomasum–duodenum transitions. In the ileum and jejunum, genes involved in lipid metabolism showed links to fatty acid profiles, whereas genes governing amino acid metabolism in the small intestine were connected to the amino acid composition of muscle. Cecum- and colon-enriched genes were linked to flavor precursor biosynthesis. Species-specific differences revealed that sheep muscle contained higher levels of key amino acids (Asp, Glu, Hyp, Cys, Tyr), whereas goats showed higher α-linolenic acid and other polyunsaturated fatty acids. This work establishes a gut–muscle transcriptomic axis in small ruminants, identifying candidate genes (e.g., GKN2, APOC3, AQP5) and pathways that may be involved in regulating amino acid, fatty acid, and flavor traits of meat quality.